EXTRACTION AND ANTIOXIDANT ACTIVITIES OF TWO SPECIES ORIGANUM PLANT CONTAINING PHENOLIC AND FLAVONOID COMPOUDS - N. Benchikha; T. Lanez; M. Menaceur; Z. Barhi (Journal of Fundamental and Applied Sciences, 2013)
The antioxidant of ethanolic extract of two species of Origanum and essential oil of plant Origanum vulgare were investigated and also the total phenolic and flavonoid content measured. The radical scavenging activity was measured using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. Total phenolic and flavonoid contents were estimated by Folin-Ciocalteu and aluminum chloride methods, respectively. According to the results the leaves extracts have very important values for polyphenols (266.86 mg GAE / g and 194.78 mg GAE / g) and high antioxidant activity; DPPH (IC50 = 1.37 g / l and IC50 = 1.53mg / l ) for species majorana, and vulgare respectively; also the DPPH of essential oil of Origanum vulgare was IC50 = 15.360 mg/l . This data suggest of these extracts as a natural source of phenolic compounds and antioxidant.